Imam al-Ghazali dan Kerangka Keilmuan Ushul al-Fiqh: Telaah terhadap al-Mustasfa min 'Ilm al-Ushul - Rohmanu, Abid (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2009)
This study aims to examine Imam al-Ghazali's contribution to the formation of the usul al-fiqh scientific framework through an analysis of his monumental work, al-Mustasfa min 'Ilm al-Ushul. Using a qualitative method with a descriptive-analytical approach, this study traces the structure of thought, methodology, and integration between philosophical rationality and Islamic scientific tradition in the work. The results of the study show that al-Ghazali succeeded in compiling a comprehensive ushul al-fiqh system by balancing between naqli evidence and aqli approach. Al-Mustasfa is considered the pinnacle of the development of the mutakallimin school of ushul al-fiqh and an important reference in the study of classical to contemporary Islamic law. This research emphasizes that al-Ghazali's contribution is not only normative, but also methodological, capable of bridging the need for ijtihad across eras.